Integrating PhET Simulations in a Cognitive Conflict Approach to Foster Critical Thinking among Pre-Service Elementary Teachers - Muhammad Ikhsan Sukaria (International Journal of Technology and Education Research, 2025)
This study aims to analyze the effect of the cognitive conflict approach assisted by PhET Interactive Simulations on the critical thinking ability of elementary education students. The research employed a quasi-experimental method with a pretest–posttest control group design. The research subjects consisted of 50 fifth-grade students from SD Negeri 61 Palongki, who were divided into two groups: an experimental class and a control class, each comprising 25 students. The research instrument was an essay-type critical thinking test developed based on the five indicators proposed by Ennis (1985). The results revealed a significant difference between the critical thinking abilities of students in the experimental and control groups, with a t value of 4.85 and p < 0.05. The average N-Gain score of the experimental group was 0.67 (moderate–high category), which was higher than that of the control group at 0.34 (moderate category). The effect size (Cohen’s d) value of 0.92 indicated a strong influence of the cognitive conflict approach assisted by PhET Interactive Simulations. These findings confirm that the integration of the cognitive conflict approach with interactive simulation media can effectively foster students’ critical thinking skills through a process of conceptual restructuring and reflection-based learning experiences.